MOLECULAR CHARACTERIZATION OF Giardia intestinalis IN HEIFER CALVES REARED IN INDIVIDUAL SHELTERS WITHIN PADDOCKS AT THE MUNICIPALITY OF PIRAÍ IN THE STATE OF RIO DE JANEIRO, BRAZIL - Fagundes, Thais Ferreira; Vidal, Letícia Gabriela Poblete; Alves, Pedro Afonso Moreira; McIntosh, Douglas; Menezes, Rita de Cássia de Alves Alcântara; da Fonseca, Adevair Henrique; Pereira, Maria Julia Salim (Brazilian Journal of Veterinary Medicine, 2014)
ABSTRACT. Fagundes T.F., Vidal L.G.P., Alves P.A.M., McIntosh D., Menezes R. C.A.A., Fonseca A.H. & Pereira M.J.S. Molecular characterization of Giardia intestinalis in heifer calves reared in individual shelters within paddocks at the Municipality of Piraí in the State of Rio de Janeiro, Brazil. [Caracterização molecular de Giardia intestinalis em bezerras criadas em abrigos individuais dentro de piquetes no Município de Piraí, Estado do Rio de Janeiro, Brasil]. Revista Brasileira de Medicina Veterinária, 35(Supl.2):17-21, 2013. Programa de Pós-Graduação em Ciências Veterinárias, Anexo 1 do Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, km 7, Seropédica, 23897-970, Brazil. E-mail: tha.fagundes@gmail.com This study aimed to characterize the G. intestinalis genotypes in heifer calves from birth to 100 days old, reared in individual shelters within paddocks in the municipality of Piraí, Rio de Janeiro State. Molecular characterization of the protozoan genotypes was performed by analyzing the β-Giardin gene via PCR (nested-PCR). Samples from 30 heifer calves positive for Giardia cysts in parasitological examinations were selected for PCR analysis, and of these samples, 10 were digested with the enzyme HaeIII. Following digestion the genotypes were confirmed by sequencing. The genotypes A and E were identified in 30% and 70% of the samples analyzed, respectively. As genotype A is infectious to humans and the affected calves can be a source of infection, this parasitosis is of great public health importance. This is the first study to characterize G. intestinalis genotypes present in heifer calves reared in individual shelters within paddocks in Rio de Janeiro State.